Development Of An IoT-Based Security System For Swiftlet Nests Using Esp32-Cam And Pir Sensor - Arbansyah, Arbansyah; Maulidina, Gina; Nur Ilham, Muhammad Fauzan; Sumadi , Muhammad Taufiq (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2025)
This study focuses on developing an Internet of Things (IoT)-based security system for swiftlet nests using ESP32-CAM and Passive Infrared (PIR) Sensors. The goal is to address the challenges of securing swiftlet nests located in remote areas, which are prone to theft and hard to monitor manually. The system combines motion detection, image capturing, and notification delivery through Telegram when connected to the internet. If the internet connection is unavailable, captured images are stored on a microSD card as an alternative. The research methodology includes the design of both hardware and software, implementation, and system performance testing. Test results show that the PIR sensor effectively detects motion within a 1-5 meter range, and the ESP32-CAM can capture and send images to Telegram in under 10 seconds when the network is stable. The system also reliably stores images on the microSD card when offline. This research highlights the system's ability to improve the security of swiftlet nests efficiently, offering a practical solution for farmers to monitor their nests in real-time without being physically present. The system’s flexibility and reliability make it a valuable tool for enhancing the security of agricultural resources.